EFFECT OF GENOTYPE AND SOWING DATE ON THE RESPONSE TO BORON IN WHEAT (Biological Sciences - PJSIR, 2022)
A field trial was conducted in an alluvial soil of8angladesh to evaluate the effect of boron on the number of grains/spike, grain yield and nitrogen content of wheat sown in different dates. The experiment comprised two 8 treatments(0 and 3 kg 8/ha), three wheat varieties (Sonalika, Kanchan and Aghrani) and four dates of sowing with 2-week intervalsbeginning from the November 15 of 1992. The experiment was laid out in split-split plot-design with sowing dateas main-plot, wheat variety as sub-plot and boron treatment as sub-sub-plot. The results showed that added 8 hadpositive efffect on the number of grains/spike and grain yield. Both grains/spike and grain yield were decreased as thedate of sowing was delayed particularly after December I, over the varieties. Among the varieties, Kanchan gavecomparatively better yield. Nutrient analysis showed that Nand 8 contents in grain were increased after B treatmentto soil indicating that 8 probably helped protein synthesis. Like grain yield, grain N level had declined with the delayingof sowing date. Such adverse effect of late sowing was thought to be related with elevated temperature prevailing atflowering stage that induced slower rate of B mobility in plant, poor number of grains/spike and lower grain yield.